Kajian Sejaran Pengembangan Ilmu Kedokteran Islam di Istac Selangor, Malaysia (1994-2002) - Nurdeng Deuraseh; Safrilsyah Safrilsyah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
International Institute of Islamic Thought and Civilization (ISTAC) was established by the Malaysian government in 1987. Assoc. Dr. Syed Muhammad Naquib al-Attas is the Founder Director (Founder-Director) the first ISTAC and given responsibility for building design and drafting ISTAC academic courses. The Institute is the only institution in Malaysia and the Islamic world who view knowledge of Islamic studies from the three perspectives of Islamic Thought (Islamic Thought), Civilisation Islam (Islamic Civilization) and Islamic Sciences (Islamic Science). These areas is suitable to learn and studied by all the background knowledge of students interested in Islamic studies from the perspective of history, historiography, philosophy, civilization and its relation to past and contemporary civilization. This paper will describe the ISTAC contribution in strengthening the medical history of Islamic knowledge based on experience of the writer as a graduate student ISTAC from 1994 to 2002.